Reconfiguring sliding-mode controller for underwater vehicles - Demirci, Ufuk. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2004., 2004)
The challenging control problem of underwater vehicles is addressed in this study under excessive sea wave disturbances at shallow submerged operation. The systems are becoming more and more complex with the effect of rapid technological developments. These complex systems require fault tolerant control systems in order to accommodate with the uncertainties caused by faults or environmental changes. In this doctoral dissertation, a novel re-configuring controller is proposed based on sliding mode methodology for fault or disturbance tolerant control. Re-configuring control with sliding mode technique annuls the unwanted effects of system uncertainties caused by faults and environmental effects and avoids the chattering by increasing the robustness of the controller when it is necessary. As a result acceptable performance is obtained in case of system uncertainties and the chattering phenomenon is eliminated for the nominal system situation.
Keywords: Oceanographic submersibles.; Sliding mode control.; Submarines (Ships); Fault location (Engineering)